Mutations in myeloid transcription factors and activated signaling genes predict chronic myeloid leukemia outcomes - Perusini, Maria Agustina; Žáčková, Daniela; Kim, Taehyung; Pagnano, Katia; Pavlovsky, Carolina; Ježíšková, Ivana; Kvetková, Anežka; Jurček, Tomáš; Kim, Jaeyoon; Yoo, Youngseok; Yi, Seongyoon; Lee, Hyewon; et al. (Blood advances, 2024)
Advancements in genomics are transforming the clinical management of chronic myeloid leukemia (CML) toward precision medicine. The impact of somatic mutations on treatment outcomes is still under debate. We studied the association of somatic mutations in epigenetic modifier genes and activated signaling/myeloid transcription factors (AS/MTFs) with disease progression and treatment failure in patients with CML after tyrosine kinase inhibitor (TKI) therapy. A total of 394 CML samples were sequenced, including 254 samples collected at initial diagnosis and 140 samples taken during follow-up. Single-molecule molecular inversion probe (smMIP)-based next-generation sequencing (NGS) was conducted targeting recurrently mutated loci in 40 genes, with a limit of detection of 0.2%. Seventy mutations were detected in 57 diagnostic samples (22.4%), whereas 64 mutations were detected in 39 of the follow-up samples (27.9%). Carrying any mutation at initial diagnosis was associated with worse outcomes after TKI therapy, particularly in AS/MTF genes. Patients having these mutations at initial diagnosis and treated with imatinib showed higher risks of treatment failure (hazard ratio, 2.53; 95% confidence interval, 1.13-5.66; P = .0239). The adverse prognostic impact of the mutations was not clear for patients treated with second-generation TKIs. The multivariate analysis affirmed that mutations in AS/MTF genes independently serve as adverse prognostic factors for molecular response, failure-free survival, and progression risk. Additionally, there was an observable nonsignificant trend indicating a heightened risk of progression to advanced disease and worse overall survival. In conclusion, mutations in the AS/MTF genes using smMIP-based NGS can help identify patients with a potential risk of both treatment failure and progression and may help upfront TKI selection.
Keywords: signální transdukce; Signal Transduction; Humans; inhibitory proteinkinas; lidé středního věku; Disease Progression; Transcription Factors; Female; mutace; mladý dospělý; dospělí; Aged; výsledek terapie; senioři; lidé; Adult; Protein Kinase Inhibitors; ženské pohlaví; Male; chronická myeloidní leukemie; Middle Aged; prognóza; Treatment Outcome; Aged, 80 and over; vysoce účinné nukleotidové sekvenování; Young Adult; High-Throughput Nucleotide Sequencing; senioři nad 80 let; progrese nemoci; transkripční faktory; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Mutation; mužské pohlaví; Prognosis